Re-configuring Community seed bank functions, by building on their social capital to incorporate landscape management and restoration - CGIAR Research Program on Water, Land and Ecosystems (2019)
During the first phase farmers used a large amount of genetic diversity for crops they selected through a participatory process. At the end 2 CSB were built which will now be used in second phase to enhance landscape restoration. One thousand farmers are part of the 2 CSB